Roger Nols: een (on)aantastbare burgemeester? - Serge Jaumain; Joost Vaesen (Brussels Studies)
Should the bust of Roger Nols be removed? The question is now being debated. This article questions the reasons why the representation and memory of the former mayor of Schaerbeek seem so obtrusive in the public space, and emphasises the need́ to place the controversial events in a broader historical context. It cautions against focusing the criticism only on him, which could exonerate those who supported racist and xenophobic discourses and policies openly or in the secrecy of the ballot box, both in Schaerbeek and in other municipalities of the capital. This reflection allows a discussion of the risks of “presentism”, i.e. the use of the past according to current political objectives without taking historical reality into account. It shows that it is not the role of historians to make a decision about the future of this bust, but that they do have an essential role to play in documenting the context surrounding this controversial figure.